Dissociation as a mechanism of psychological defense in adapting to a different cultural environment - N. A. Bokhan; A. A. Ovchinnikov; A. N. Sultanova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
In the theoretical part, the authors focus on specific issues in the diagnosis and treatment of patients migrants with dissociative symptoms related to the cultural specialty of the settings in the etiology of emerging symptoms and for psychotherapeutic interventions. With the use of the scale dissociation (DES) were identified reliable differences in the sample of labour migrants and of migrants-compatriots in the MannWhitney criterion p